Produ??o do cuidado ? pessoa com doen?a falciformena aten??o prim?ria de sa?de - Andrade, Lorena Marques Oliveira (2017)
The production of sickle-cell care (SCD) in Primary Health Care (PHC) is important since it encompasses the established relationship between health professional-user in the search for the transformation of health practices centered on the user and their needs. The purpose of this study was to analyze the production of health care in PHC to the person with SCD in the institutional and technical dimensions and to understand the process of articulation between the Cities? Reference Center for People with Sickle Cell Disease (CRPSCD) and other health services for the production of health care for the person with sickle cell disease. For that, we started the study with the discussion about the historicity of PHC in Brazil and in the world and the main current conceptions. Subsequently, we discuss the production of health care based on access, reception, bonding, accountability, professional training and resolubility. This is a qualitative study, with a critical analytical approach, in the Hermeneutic-Dialectic perspective, with scenarios such as the CRPSCD, Matinha?s Family Health Unit, Dom Pedro de Alc?ntara Hospital and the Child State Hospital. The participants were made up of three groups: users assisted in the health care network to the person with SCD (group 1), health professionals working in the services surveyed (group 2) and managers of the CRPSCD, Basic Health Units and Basic Care (group 3), totaling 23 participants. We used as data collection techniques the semi-structured interview, systematic observation and analysis of documents and as a method of data analysis Hermeneutics-Dialectic. From the comparison of the data, two categories emerged: 1 - THE PRODUCTION OF CARE IN PHA TO THE PERSON WITH FALCIFORM DISEASE: (Un) articulation between the institutional and technical dimensions; 2 - INTERRELATION BETWEEN THE CRPSCD AND HEALTH SERVICES IN THE PRODUCTION OF CARE FOR THE PERSON WITH FALCIFORM DISEASE: incipient implantation, with no established counterpart and fragility in management. As for the production of PHC care for the person with SCD, the results showed a lack of PHC on the part of the users, as well as their fragility in being constituted as a preferential gateway in the system, with the reception being given to people with SCD restricted in the way is received, without establishment of relations of bond with user and low resolubility of health problems. Regarding the disarticulation of the CRPSCD with other services we cite the difficulties to perform examinations with high technological density and / or other procedures; lack of articulation and communication of PHC services and other levels of assistance; the reference system and incipient or non-existent counter-reference; high professional turnover; the emergency and emergency service unprepared in the care of people with SCD; the restricted financial resources for maintenance and expansion of the service; the invisibility of the disease in municipal plans and in the management report. We consider it necessary to organize the PHC and the service network for the production of care for people with sickle cell disease, in search of the resilubility of the health needs of these people